Tinjauan Komprehensif Tentang Manajemen Termal dan Pembuangan Panas pada Rem Cakram Otomotif: Kemajuan Dalam Bahan, Desain, dan Teknik Pemodelan - Rama Widjaja Sikumbang; Hadi Pranoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstract: The braking system is a critical component in vehicles, ensuring effective and safe deceleration. Disc brakes, commonly used in automotive applications, generate significant heat during operation, which if not managed properly, can lead to serious problems such as brake fading and component failure. This study reviews various methodologies and findings from previous research on thermal management in disc brakes using Finite Element Analysis (FEA) and other experimental methods. Key findings include the effectiveness of improved ventilation designs, the impact of cooling fins, and the role of composite materials in enhancing heat dissipation. The study also examines the influence of geometric design variations and operating conditions on thermal performance. The results highlight that advanced materials like ceramics, cross-ventilated rotors, and active cooling fins significantly improve thermal efficiency and reduce overheating risks. Furthermore, mathematical modeling techniques such as Response Surface Methodology (RSM) and Distance Weighted Least Squares (DWLS) fitting models provide valuable insights for optimizing disc brake systems. The review underscores the importance of comprehensive thermal management strategies to ensure the safety and reliability of braking systems under various operational conditions. Future research should focus on addressing the limitations of current FEA models and developing more efficient materials and rotor designs. Keywords: Braking System, Thermal Management, Finite Element Analysis